Effect of Service Quality and Relational Marketing on Consumer Purchasing Decisions at PT. Garuda Teladan Biscuid Binjai North Sumatra. - Situmorang, Irvan Rolyesh (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
The purpose of this study is to find out the influence of Service Quality, Relational Marketing on Consumer Purchasing Decisions there is PT. Garuda Teladan Biscuid Binjai North Sumatra. Population in research at PT. Garuda Teladan Biscuid Binjai North Sumatra as many as 157 respondents. The sample was obtained by 61 respondents. The sampling technique uses Simple Random Sampling. data sources in this study from primary data collection techniques, namely observations, interviews, and questionnaires. The data analysis technique used is multiple linear regression analysis.The results of the partial research are quality of service has a positive and significant effect on Consumer Purchasing Decisions. Relational Marketing has a positive and significant effect on Consumer Purchasing Decisions. Simultaneously obtained Quality of Service and Relational Marketing affects Consumer Purchasing Decisions. The results of the R Square Test showed that the Quality of Service and Relational Marketing had an influence of 81.5%, while the remaining 18.5 was influenced by other factors not included in this study such as Price, Promotion, Products, and so on